Design and Build Hydroponic Installations and Applications Using IoT-Based Multisensors with Solar Panel Electrical Energy - Tony Melkysedek; Emilia Hesti; Irma Salamah (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2023)
This research designs an IoT-based hydroponic installation using a NodeMCU 8266 microcontroller equipped with multi-sensors such as temperature, humidity, air pressure, flow, pH, TDS (Total Dissolved Solid), and EC (Electrical Conductivity) sensors that will be wirelessly connected to controlling devices using Arduino IDE, Firebase, and MIT APP Converter software and using renewable energy in the form of Solar Panels. The expected result is the creation of innovation in the field of agricultural technology, especially in plant cultivation techniques with hydroponics. With this tool, the user can fully monitor all information about the state of the plant-growing environment. From the tests that will be carried out later, researchers hope to produce test data on every sensor reading, pump motor activation, and data delivery response from application from tool and otherwise.